ESQUEMAS COGNITIVOS NO ENSINO DA LÍNGUA INGLESA: DESENVOLVENDO COMPETÊNCIAS LINGUÍSTICAS - Siqueira, Liz Behr (2020)
The objective of this work was to discuss how a foundation in the proposal of cognitive schemes can contribute to the development of language skills in high school English language classes. The research, characterized as qualitative, bibliographic and documentary analysis, sought to: a) conceptualize cognitive schemes based on the theoretical assumptions of Wittgenstein, Piaget and Morin's theory of complexity; b) to analyze and compare the approaches present in the area of Languages, Codes, and their Technologies, according to the BNCC and in the Curricular Matrices of Basic Education of Marist Brazil; and c) to verify how didactic sequences in the area of Languages, Codes, and their Technologies and more specifically in the teaching of the English Language of high school of the Marist College Santa Maria activate the cognitive schemes. It also aimed to propose, apply, and analyze a didactic sequence based on Nussbaum's perspective, to point out alternatives to possible gaps found in the analyzed materials. Based on the results, we highlight the possibilities of performing the integral education of students through the activation of pre-existing cognitive schemes and their relationship with new schemes proposed. This study allowed reflection on the act of teaching in an innovative, critical, and reflective way and created possibilities of a teaching-learning focused on the individual's whole.